Role of Magnesium Supplementation in Children with West Syndrome: A Randomized Controlled Clinical Trial - Yadav, Vijay Kumar; Amrita, Amrita; Yadav, Sunita; Kumar, Rajeev; Yadav, Krishna Kumar (Iranian Journal of Child Neurology, 2022)
Abstract Objectives West syndrome is a severe epileptic encephalopathy of young age. It is characterized by a clinico-electrical triad of infantile epileptic spasms, regression or arrest of psychomotor development, and hypsarrhythmia. In the last two decades, the large progress in the development of newer antiepileptic drugs has allowed us to have a vast choice of treatment options to control spasms, although they often fail to do so. Thus, there is a need to explore other treatment options. Materials & Methods Subjects in this open-labelled randomized control trial were included newly diagnosed children of age between 3 months and 5 years of both genders. A total of 52 children were recruited and randomized into two groups: an intervention group (n=30) and a non-intervention group (n=22). Magnesium sulphate was provided for the intervention group but not for the non-intervention one. Both groups received the rest of the treatments, including adrenocorticotropic hormone and antiepileptic drugs. The follow-up period was three months, at the end of which a per-protocol analysis was performed. Results There was no significant difference in seizure control and neurodevelopmental outcome between both groups, but electroencephalogram significantly improved in the intervention group compared to the control. Also, the clinical response was better in patients with normal initial serum magnesium levels in the intervention group (p=0.003) than in other patients. Conclusion Magnesium supplementation may be helpful in children with West syndrome